Pectin-Rich Amendment Enhances Soybean Growth Promotion and Nodulation Mediated by Bacillus Velezensis Strains - Hassan, Mohammad K.; McInroy, John A.; Jones, Jarrod; Shantharaj, Deepak; Liles, Mark R.; Kloepper, Joseph W. (Plants (Basel), 2019)
Plant growth-promoting rhizobacteria (PGPR) are increasingly used in crops worldwide. While selected PGPR strains can reproducibly promote plant growth under controlled greenhouse conditions, their efficacy in the field is often more variable. Our overall aim was to determine if pectin or orange peel (OP) amendments to Bacillus velezensis (Bv) PGPR strains could increase soybean growth and nodulation by Bradyrhizobium japonicum in greenhouse and field experiments to reduce variability. The treatments included untreated soybean seeds planted in field soil that contained Bv PGPR strains and non-inoculated controls with and without 0.1% (w/v) pectin or (1 or 10 mg/200 μL) orange peel (OP) amendment. In greenhouse and field tests, 35 and 55 days after planting (DAP), the plants were removed from pots, washed, and analyzed for treatment effects. In greenhouse trials, the rhizobial inoculant was not added with Bv strains and pectin or OP amendment, but in the field trial, a commercial B. japonicum inoculant was used with Bv strains and pectin amendment. In the greenhouse tests, soybean seeds inoculated with Bv AP193 and pectin had significantly increased soybean shoot length, dry weight, and nodulation by indigenous Bradyrhizobium compared to AP193 without pectin. In the field trial, pectin with Bv AP193 significantly increased the shoot length, dry weight, and nodulation of a commercial Bradyrhizobium japonicum compared to Bv AP193 without pectin. In greenhouse tests, OP amendment with AP193 at 10 mg significantly increased the dry weight of shoots and roots compared to AP193 without OP amendment. The results demonstrate that pectin-rich amendments can enhance Bv-mediated soybean growth promotion and nodulation by indigenous and inoculated B. japonicum.